Active control behavior on the flow pattern in a circular duct. (2022) - Khan, Sher Afghan; Ridwan,; Mokashi, Imran; Kumar, Arvind; Suheel J.I,; Faheem, Mohammed
Abstract: The current analysis aims to review the effectiveness of the flow regulations at Mach 1.87, a considerably large Mach number. The duct radius is11 mm, and the diameter ratio concerning the exit of the nozzle is 2.2. Tests were done at different expansion levels for eight different duct sizes. Here we are pondering in a situation where there is a considerable variation of pressure is noticed. The flow control was located at a PCD of 13 mm from the axis. The control jets of 0.001 m diameter producing a Mach unity jet, used as energetic flow control. For shorter tube sections at smaller NPRs, the pressure undertakes a minimal value. Soon After, with an increase of the tube size and expansion levels, a continuing fall in pressure owing to the decline in the level of adverse pressure and shock waves intensity. Flow fluctuations are witnessed for various duct sizes. The duct size represents a vital part while ascertaining the flow advancement in the duct. Relatively high pressure is seen for duct length L = 132 mm and L = 220 mm for nozzle pressure ratios three and five. The pressure becomes modest due to the effect of duct size. For NPR = 7, an increase in pressure is restricted by the separated zone, and atmospheric restrictions are almost accomplished. For the 10D duct, the realization of the ambient condition is additionally enhanced near the upstream.